Transformational Leadership and Innovative Work Behavior: The Mediation-Moderation Model of Ambidextrous Culture - Lukitasari, Dania; Etikariena, Arum (Universitas Islam Indonesia, 2024)
In the Volatility, Uncertainty, Complexity, and Ambiguity (VUCA) era, organization in complex businesses and competitive environments with unprecedented challenges and opportunities. In this context, the development of innovation is required to survive throughwork behavior. Therefore, this research aimed to explore the influence of transformationalleadership on work behavior of employees, considering meaningful work as a mediating variable. The moderating role of ambidextrous organizational culture is also tested on ASN (civil servant) at the Indonesia Ministry of X (N = 210) using the self-report data collection method. The data were analyzed using the PROCESS Model 15 statistical method developed by Hayes. The result showed that meaningful work mediated the relationship between transformational leadership and innovative work behavior (B = .50, CI 95% [.15, .42]). Moreover, ambidextrous organizational culture played a significant role as a moderator of the direct relationship between the variables (B = .3449, p < .05), but does not play a role in the indirect relationship (B = -.1292, p > .05). Practical and innovative contributions were also provided to practitioners of industrial and organizational psychology, as well as ASN in exploring innovative work behavior.